2023
DOI: 10.3390/atmos14040623
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Belgian Airborne Sniffer Measurements in the MARPOL Annex VI Enforcement Chain

Abstract: The Royal Belgian Institute of Natural Sciences launched its airborne sniffer program in 2015 whereby a custom-built sniffer sensor was installed onboard the Belgian coastguard aircraft enabling the measurement of SO2 and NOx emitted by ocean-going vessels (OGVs). The data gathered on non-compliant OGVs were subsequently sent to port inspection authorities, who were then able to trigger inspections more rapidly than had they not had the data from the aircraft. This study reveals the added value of airborne ale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Given the limited number of Tier III vessels currently in operation, the NECA implementation has not yet made a signi cant impact in reducing average NO x emission factors. Furthermore, previous studies already indicated increased NO x emission factors for Tier II vessels compared to Tier I vessels 14,24,29,33,39,40 . Consequently, the outcomes of this study align closely with the conclusions drawn from other research studies.…”
Section: Discussionmentioning
confidence: 88%
“…Given the limited number of Tier III vessels currently in operation, the NECA implementation has not yet made a signi cant impact in reducing average NO x emission factors. Furthermore, previous studies already indicated increased NO x emission factors for Tier II vessels compared to Tier I vessels 14,24,29,33,39,40 . Consequently, the outcomes of this study align closely with the conclusions drawn from other research studies.…”
Section: Discussionmentioning
confidence: 88%
“…From 2015 onwards, the Royal Belgian Institute of Natural Sciences (RBINS) has been conducting airborne surveillance operations for the monitoring of Regulation 14 of MARPOL Annex VI concerning sulphur emissions from OGVs [47,50,74]. The RBINS expanded its monitoring efforts in 2020 to include Regulation 13 of MARPOL [47,56].…”
Section: Resultsmentioning
confidence: 99%
“…During the monitoring period from July 2015 to November 2022, the RBINS conducted 414 flights and 645 operational flight hours, making approximately 10446 low passes in the exhaust plumes of 7536 OGVs, measuring 6954 OGVs' FSC and 2353 OGVs' NOx emission [47,50,56,74] The predominant type of measured OGVs were container OGVs (31%), followed by tanker OGVs (29%), general cargo and bulk carrier OGVs (20%) and passenger and Roll On Roll Off (RORO) OGVs (15%;). Regarding NOx monitoring, the majority of monitored OGVs were Tier I OGVs (52.6%); followed by Tier II OGVs (37.5%); Tier 0 OGVs (9.6%) and Tier III OGVs (0.3%).…”
Section: Belgian Airborne Monitoring Datasetmentioning
confidence: 99%
“…From 2015 onwards, the RBINS has been conducting airborne surveillance operations for the monitoring of Regulation 14 of MARPOL Annex VI concerning sulphur emissions from OGVs [47,50,75]. The RBINS expanded its monitoring efforts in 2020 to include Regulation 13 of MARPOL [47,56].…”
Section: Resultsmentioning
confidence: 99%